2014
DOI: 10.1186/1471-2431-14-38
|View full text |Cite
|
Sign up to set email alerts
|

Pancytopenia as an early indicator for Stevens-Johnson syndrome complicated with hemophagocytic lymphohistiocytosis: a case report

Abstract: BackgroundStevens-Johnson syndrome (SJS) is a severe skin and mucosal bullous disease. When complicated with Hemophagocytic lymphohistiocytosis (HLH), the condition is especially life-threatening.Case presentationHere we report the case of a 4-year-old boy suffering from SJS with extensive erythema multiforme and bulla. Despite active intervention and supportive care, the boy experienced increased skin lesions and a higher fever. Meanwhile, decreases in white blood cell count and hemoglobin were observed. Hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…Our study revealed that serum ferritin level has a predictive value for the severity of drug eruptions in the early stage. It was significantly higher in the SCADRs group compared with the non‐SCADRs group, a result that is consistent with some case reports and studies showing the association between hyperferritinemia and drug eruptions in SJS and DRESS . The association between ferritin and some variables, which may reflect the severity of drug eruptions and physical condition of patients, was observed.…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed that serum ferritin level has a predictive value for the severity of drug eruptions in the early stage. It was significantly higher in the SCADRs group compared with the non‐SCADRs group, a result that is consistent with some case reports and studies showing the association between hyperferritinemia and drug eruptions in SJS and DRESS . The association between ferritin and some variables, which may reflect the severity of drug eruptions and physical condition of patients, was observed.…”
Section: Discussionsupporting
confidence: 90%
“…Our patient's favorable outcome is consistent with other pediatric case reports . One patient relapsed , but was effectively managed, demonstrating the need for close surveillance.…”
Section: Discussionsupporting
confidence: 88%
“…Our case describes a boy with a confirmed viral and bacterial prodrome, followed by a presumptive immune drug response. A two-hit hypothesis has support in three other cases [12,13,16], whereby nonspecific viral upper respiratory tract symptoms temporally overlapped with medications commonly implicated with TEN. Two other TEN cases [11,17] reported no mucosal involvement and isolated EBV from the skin lesions, suggesting a single viral entity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The causative agents in most reported cases are antibiotics or anticonvulsants including trimethoprim–sulfamethoxazole, vancomycin, phenytoin, phenobarbital and lamotrigine 2 3. HLH is mostly associated with severe hypersensitivity reactions such as Stevens-Johnson syndrome, toxic epidermal necrolysis4 or drug reactions with eosinophilia and systemic symptoms 2. These reactions form part of the type 4 delayed-hypersensitivity reaction, which involves activation of drug-specific T cells.…”
mentioning
confidence: 99%